Amplified itch: a proposed phenomenon adopted from pain medicine. Issue 2 (April 2020) - Fleischer, Alan B.
Abstract : Pain and itch are both similar sensory modalities through which we interact with the environment. Amplified pain is characterized by pain that is out of proportion to the history and physical findings. Amplified pain recognizes that some patients with chronic pain undergo signal amplification. I postulate the existence of amplified itch, in which the experience and the expectation of itch exacerbates itch. These patients should be more treatment-refractory and may not achieve complete itch control. Condition awareness could improve the care of these patients by helping us to consider alternative treatment. Analogous to amplified itch treatment, itch acceptance, and other psychotherapeutic interventions may prove to be valuable approaches.